Nonalcoholic fatty liver disease is associated with a decreased myocardial mechano‐energetic efficiency. (30th July 2020) - Fiorentino, T. V.; Miceli, S.; Succurro, E.; Sciacqua, A.; Andreozzi, F.; Sesti, G.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is linked to a raised risk of cardiovascular diseases (CVD), although the underlying mechanisms are not completely known. A reduced myocardial mechano‐energetic efficiency (MEE) has been found to be an independent predictor of CVD. Objective: To evaluate the association between NAFLD and a compromised MEE. Methods: Myocardial MEE was assessed by a validated echocardiography‐derived measure in 699 nondiabetic individuals subdivided into two groups according to ultrasonography defined presence of NAFLD. Results: Subjects with NAFLD displayed higher levels of systolic (SBP) and diastolic blood pressure (DBP), triglycerides, fasting and postload glucose, high‐sensitivity C‐reactive protein (hsCRP), insulin resistance (IR) estimated by HOMA‐IR and liver IR index, and lower values of high‐density lipoprotein (HDL) in comparison with those without NAFLD. Presence of NAFLD was associated with increased levels of myocardial oxygen demand and reduced values of MEE. MEE was negatively correlated with male sex, age, BMI, waist circumference, SBP, DBP, total cholesterol, triglycerides, fasting and postload glucose, HOMA‐IR and liver IR index, hsCRP and positively with HDL levels. In a multivariable regression analysis, presence of NAFLD was associated with MEE regardless of several cardio‐metabolic risk factors such as age, gender, waist circumference, SBP, DBP, total and HDL cholesterol, triglycerides, glucose tolerance and hsCRP ( β = −0.09, P = 0.04), but not independently of IR estimates. Conclusion: Ultrasound‐defined presence of NAFLD is associated with a decreased MEE, a predictor of adverse cardiovascular events. The relationship between NAFLD and a compromised MEE is dependent of IR. Abstract :